Development of a Conveyor-Based Practice Performance Assessment Tool with Android Control to Improve Vocational High School Students' Work Readiness - Ghozali, Fanani Arief; Tentama, Fatwa; Sudarsono, Bambang; Syamsuddin, Arief; Setyanto, Barry Nur; Bhakti, Wirayudha Pramana (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2023)
The unemployment rate for vocational high school graduates is still very high. Unemployment occurs because the level of work readiness is still low. Work readiness can be improved by applying competence mastery-oriented learning. Competence that is complete requires measurement tools or assessment of student work competencies to measure competency success. Therefore, this study aims to: (1) produce a product in the form of a practical performance assessment tool for students in the conveyor-based pandemic era with android control; (2) know the quality and performance of the developed tools; This research is development research using the method of combining the waterfall method and Borg & Gall. This research focuses on product functionality so that testing is carried out by technicians with input from experts from the industry. The research data were obtained from observations, interviews, document studies, and questionnaires. The results of this study are as follows: (1) the product developed already has basic functions and can be operated using Android; (2) the results of testing by technicians from the aspects of functionality, reliability, efficiency, maintainability, and portability obtained a conformity percentage of 90% (Very Good), so that the tool can be used to test student work readiness in vocational schools or training institutions.